Speech Therapy and Self-awareness About Stuttering for Adults Who are Stutters in Pakistan - Faiza Iqbal; Muhamad Dzahir Bin Kasa; Yahya Don (Universitas Muhammadiyah Sidoarjo, 2020)
All over the world extra than 70 pile human beings whichever stutter, who is in relation to 1% on the population (Bloodstein & Bernstein-Ratner, 2008). Recent research bear referred to troubling findings related to the cognitive, affective, and communal blessing over human beings who stutter people who stutters. The level of understanding among adult stutters in Pakistan concerning the problem of stuttering Awareness and speech therapy. For this study, cross sectional study design was used. Research has been conducted in Govt. and private sector tertiary care Hospitals in Lahore Pakistan. The study is completed within four months from December 2018 to February 2019. Between the ages of Dec 2018 to March 2019, adult stuttering clients were taken, over 15 years of age. Inclusion requirements included all the males and females above 15 years of age who were stuttering. This involves pupils, males and females with blockage, delay, prolongation or any other primary or secondary signs stuttering. Both congenital or chronic disease stutters were ruled out. All patients were briefly interviewed before they were considered as part of the study to ensure that they met the criteria for inclusion. A Performa was established and validated by 10 experts after literature review and expert opinion (having a minimum of 5 years of field experience). There is a significant correlation between Understanding regarding the Stuttering issues and understanding of Stuttering Self Therapy. Awareness on the issue of Stuttering on the understanding of speech therapy for Stutter individuals is shown to be substantially successful. These approaches of speech therapy differ by individual because of the differences between them. It was also found that the more stutter has knowledge of his question with expression the more he performs and utilizes psychological self-help strategies. The study was conducted only on adult stutters. It was a short-run analysis. Sample was taken from a single Pakistani city. Large-scale analysis should be performed for large sample size. The research should include more than in Pakistani city population. Research may also involve children who stutter in future research.